2020
DOI: 10.21203/rs.3.rs-37946/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating knowledge, attitudes, and practices related to COVID-19 outbreak among Bangladeshi young adults: A web-based cross-sectional analysis

Abstract: Abstract Aim: This study aimed to assess knowledge, attitudes, and practices (KAP) towards COVID-19 among young adults in Bangladesh. Subject and Methods: A cross-sectional survey was conducted from 5th May to 25th May 2020. Young adults aged between 18-35 years were approached via social media to complete an online questionnaire consisted of socio-demographic characteristics and KAP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
11
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 15 publications
12
11
3
Order By: Relevance
“…Although most of the SAAOs had good knowledge of about COVID-19, there is still need to increase knowledge of about 33.64 percent of them ( Table 3). However, our good knowledge score is higher than the previously recorded good knowledge among Bangladeshi people [20,22], but lower than the Chinese people [2]. Our findings differ with a study [24], reporting inaccurate knowledge of the people of Bangladesh about COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although most of the SAAOs had good knowledge of about COVID-19, there is still need to increase knowledge of about 33.64 percent of them ( Table 3). However, our good knowledge score is higher than the previously recorded good knowledge among Bangladeshi people [20,22], but lower than the Chinese people [2]. Our findings differ with a study [24], reporting inaccurate knowledge of the people of Bangladesh about COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…The possible explanation could be that the respondents were relying heavily on social media during the lockdowns, and this can be justified by a study [28], reporting that the use of internet has been increased by 15-20 percent during the lockdowns in Bangladesh. Some other studies [19][20] reported similar to our finding. Next to the social media, television and friends and family were important information sources of COVID-19 ( Figure 2).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations